Preoperative White Blood Cell-Related Indicators Can Predict the Prognosis of Patients with Transurethral Resection of Bladder Cancer - Gao M; Yang Q; Xu H; Chen Z; Wang X; Guo H (Dove Medical Press, 2022)
Mingde Gao1 *, Qiuxing Yang2 *, Haifei Xu,1 Zhigang Chen,1 Xiaolin Wang,1 Haifeng Guo1 1Department of Urology, Affiliated Tumor Hospital of Nantong University & Nantong Tumor Hospital, Nantong, 226361, People's Republic of China; 2Department of Central Laboratory, Affiliated Tumor Hospital of Nantong University & Nantong Tumor Hospital, Nantong, 226361, People's Republic of China* These authors contributed equally to this workCorrespondence: Xiaolin Wang; Haifeng Guo, Department of Urology, Affiliated Tumor Hospital of Nantong University & Nantong Tumor Hospital, Nantong, 226361, People's Republic of China, Tel +86 159 5086 8500 ; +86 138 1360 3975, Email cxhwyc2010@163.com; 13813603975@163.comIntroduction: Numerous studies, including bladder cancer (BLCA), have confirmed the relationship between conventional systemic inflammatory biomarkers and the prognosis of tumors. Leukocytes, as the most common factor in inflammatory indicators, have been reported to predict prognosis in other tumors. However, we have not seen this research in BLCA. Therefore, we aim to find new blood markers to predict the prognosis of patients with transurethral resection of bladder tumor (TURBT).Methods: Two cohorts from the two different hospitals were used for the specific study. The best cutoff values of leukocytes-related indicators were determined according to the ROC curve. Univariate and multivariate Cox regression analysis were used to explore the impact of indicators and clinical features on prognosis for patients with TURBT. The KM curve was used to show the impact of indicators on the prognosis. According to the consequence of multivariate method, a risk model was established to evaluate the prognosis of patients with bladder cancer.Results: The white blood cell-to-lymphocyte ratio (WLR), the white blood cell-to-hemoglobin ratio (WHR), the white blood cell-to-neutrophil ratio (WNR), the white blood cell-to-monocyte ratio (WMR) and the white blood cell-to-erythrocyte ratio (WRR) are related to the prognosis of BLCA. The new risk model consisted of WHR, WMR and platelet-to-lymphocyte ratio (PLR), and patients with TURBT in the high-risk group had a worse prognosis.Conclusions: Leukocyte-related preoperative indicators could predict the prognosis of the patients with TURBT and provided some guidance for clinical workers.Keywords: bladder cancer, BLCA, white blood cell-to-lymphocyte ratio, WLR, white blood cell-to-hemoglobin ratio, WHR, white blood cell-to-neutrophil ratio, WNR